Fundamental Values of the Healthcare and Medical Education System: Evolution of the Iranian-Religious Progress Model - Tabatabai, Shima (Journal of religion and health, 2021)
Iranian culture and religious teachings lead to a unique value-laden model in health and medical education systems. This research aimed to determine these fundamental values. To identify the health system values in the religious context of Iran, a mixed critical analysis-synthesis method was conducted. Furthermore, a focus group discussion with experts was conducted. Finally, we determined the fundamental values for the Iranian-religious progress model of health care and medical education. God centeredness, spirituality, divine and religious belief, ethical virtues, health centeredness and promoting all dimensions of human health, justice, protecting the human dignity, protecting health-related rights, social accountability, community centeredness, and scientific authority (excellence) are the values that should be considered to complete the value statement of the Iranian-religious progress model of health care and medical education.